Decidualization of endometriosis in macaques - Atkins, HM (Vet Pathol, 2016)
The decidua is the superficial portion of endometrium that transforms, or decidualizes, under the influence of progesterone to nourish the early embryo during pregnancy. Deciduae outside of the uterus are found in nearly 100% of human pregnancies. This condition known as deciduosis may mimic malignancy, resulting in additional diagnostic procedures that place the mother or baby or both at risk. Deciduosis has been described in both Old and New World nonhuman primates in conjunction with pregnancy and after treatment with exogenous progestins. Here the authors present 6 cases of deciduosis associated with endometriotic lesions in female rhesus and cynomolgus macaques (Macaca mulatta and Macaca fascicularis). Full diagnostic necropsies with histological analyses were performed on all animals. Deciduae were stained with hematoxylin & eosin and by immunohistochemistry for vimentin, CD10, progesterone receptor, estrogen receptor, desmin, cytokeratin, kermix P8, chorionic gonadotropin, human placental lactogen, and calretinin. The most common clinical signs were abdominal pain (4 of 6) and anorexia (2 of 6). At necropsy, macaque uteri were often enlarged or disfigured (4 of 6) with abundant fibrous adhesions (5 of 6). Affected tissue consisted of epithelial-lined cysts and decidualized stroma with scattered gamma/delta T cells. Decidualized stromal cells were large and polyhedral with abundant cytoplasm and round, vesicular nuclei. They stained positive for vimentin, CD10, progesterone and estrogen. In summary, these cases illustrate deciduosis in 6 nonhuman primates with endometriosis. Understanding decidualization in nonhuman primates will aid in elucidating the pathophysiology of deciduosis during pregnancy or endometriosis and potentially lead to new interventions.